TO THE COMPARATIVE EVALUATION OF THREE-UNIT LORRY CONVOYS OF THE DIFFERENT COMPONENT SYSTEMS BY MANEUVERABILITY - Volodymyr SAKHNO; Viktor POLIAKOV; Oleg LYASHUK; Igor MUROVANYI; Valeriy STELMASHCHUK; Vasyl ONYSCHUK; Oleg TSON; Natalia ROZHKO (Scientific Journal of Silesian University of Technology. Series Transport)
The article deals with the maneuverability of three-link road trains with various layout schemes. If a train has more than three links, difficulties arise in that the study of the movement of such a multi-link vehicle is significantly complicated due to the need to take into account the influence of a significant number of factors on the nature of the movement of all links. The interaction of neighboring units in the movement of a train is eventually distributed to the entire vehicle and causes certain deviations of the components of the train (modules) from the direction of movement specified by the driving link (tractor). Considering that a road train as a motor vehicle is a means of increased danger, when solving problems about the possibility of operating three- and multi-link road trains, it is one of the first to take steps towards theoretical studies of their maneuverability, the results of which will be the basis for answering many technical, organizational, and legal questions. Analysis of the calculation results showed that in the established circular path with the selected gear ratios of the control drives, none of the road trains met the requirements of DIRECTIVE 2002/7 / EC. From this, it follows that for three-link road trains, a fundamentally different control drive is needed, which can be a double control drive.